Струится теплый свет души...: (воспоминания о З. А. Богомоловой) / Н. Д. Украинец - Украинец Николай Дмитриевич (Бон Анца, 2013)
Экземпляры: кр (20170920) / Инвентарный номер: 39446 / Цена: / Авт.знак: У 45 / ГРНТИ: 17 / ББК: 83.3(2Рос=Удм)